Begonia xenos—a new species and an updated checklist of Begonia in Laos - Lin, Che-Wei; Phonepaseuth, Phongphayboun; Rahm, Peter (Phytotaxa, 2022)
This study provides an updated list of Begonia occurring in Laos, and a new species is added to the checklist. The new taxon, Begonia xenos C.W.Lin, Phonep. & Rahm is similar to B. sinofloribunda Dorr in habit and leaf shape, but the new species differs in its staminate flowers having 4 tepals (vs. 2) with slightly crenulate (vs. entire) margins, pistillate flowers with 5 tepals (vs. 2 or 3) and a 2-locular (vs. 3-locular) ovary.